ANALISIS PERCEPATAN PELAKSANAAN PROYEK UNIT LAYANAN KANKER TERPADU RSUD BALI MANDARA DENGAN METODE FAST TRACK - Dharmayanti, G.A.P Candra; Putera, I Gusti Agung Adnyana; Prasetya, Made Yoga (Jurnal Ilmiah Teknik Sipil; Jurnal Ilmiah Teknik Sipil, Vol. 25, No. 1, Januari 2021DO - 10.24843/JITS.2021.v25.i01.p10, 2021)
Unit Layanan Kanker Terpadu RSUD Bali Mandara construction project has a building area of 4.272,74 m2. Projects with a contract value of Rp52.364.056.071 began work on May 6, 2019, and planned to finish on December 1, 2019. At the time of the study, the project progress report up to the 12th week showed a 3,76% delay in project implementation. This affects the project completion time and the contractor may be subject to penalty for the delay. This study’s purpose to design a schedule to get the acceleration of construction time using the fast track method and compare the results obtained by the conditions of project implementation experiencing delays. Secondary data used include time schedules, budget plans (RAB), weekly reports of supervisory consultants, analysis of contractor unit prices, and project drawings. The value of the implementation budget plan (RAP) is Rp45.917.529.226,76 calculated based on the RAB of the contractor without taxes and profits. The results of the analysis using the fast track method show that the project can be accelerated so that it can be finished according to the planned schedule by accelerating by 59 days (22,7%) from the duration of project implementation in a late condition (without acceleration). In terms of cost, project implementation in a late condition incurs more costs than the project implementation using the fast track method. The magnitude of the additional costs of implementing the project with a late condition of Rp2.656.202.803,55 or 5,468% more than the application of the fast track method. The application of the fast track method results in changes in the number of workers and material procurement needs at a time caused by the time shifts in activities implemented out in parallel.